Analisis Swot Lembaga Pendidikan - Marjohan Marjohan; Cucu Atikah (Journal on Education, 2024)
Strategic decision making is always related to the development of an organization's vision, mission, goals and program policies. The use of this SWOT analysis is expected to be able to see how much influence it has on improving the quality of education in schools. The research method in this research is literature review research. The data obtained is collected, analyzed and concluded to obtain conclusions regarding the literature study. SWOT analysis is strengthened by internal environmental analysis (ALI) and external environmental analysis (ALE). Strength factors in educational institutions are special competencies or other advantages that result in added value or comparative advantage of the educational institution. This can be seen if an educational institution must have skills that can be distributed to students, the best graduates/reliable results, as well as other advantages that make it superior to competitors and can satisfy stakeholders and customers (students, parents, society and nation).